The effect of condenser temperature on the performance of the evaporator in a wickless heat pipe performance. (September 2021) - Yu, Jiaheng; Nguyen, Thao T.T.; Pawar, Anisha; Wayner, Peter C.; Plawsky, Joel L.; Chao, David F.; Sicker, Ronald J.
Highlights: Study the effect of condenser temperature on the performance of a wickless heat pipe. Performance in microgravity declined as the condenser temperature decreased. Temperature data was used to extract a heat transfer coefficient in the evaporator. Nusselt number was found to scale with Marangoni number to the -1/3 power. A single correlation using the Marangoni number collapsed all the experimental data. Abstract: The Constrained Vapor Bubble (CVB), a simple, wickless, heat pipe design that depends on interfacial forces to drive corner flow in a square cuvette, was studied in the microgravity environment aboard the International Space Station (ISS). In this paper, we consider the effects of different condenser temperatures on the heat transfer and fluid flow behavior using pentane as the working fluid. As the condenser temperature was decreased, the performance of the system decreased. This performance decrease using the pure working fluid was opposite to the behavior observed when using a mixture of 94 vol% pentane and 6 vol% isohexane. The mechanism for the decline in performance as the condenser temperature was lowered was a stronger than expected increase in the apparent strength of Marangoni flows at the heater end of the system. A simple mathematical model was fit to the experimental data and used to extract an evaporator heat transfer coefficient for experiments where we held the condenser temperature constant while increasing the heater power and where we held the heater power constant while decreasing the condenser temperature. All the results could be collapsed onto a single Nusselt number vs. Marangoni number curve. In this formulation, the Nusselt number was found to decrease with increasing Marangoni number to the 1/3 power.